A Systematic Literature Review on Analytic of Costing System Design - Haervi Yunira; Emi Masyitah; Nurul Izzah Lubis; Citra Windy Lubis (Ridwan Institute, 2023)
This paper aims to find, discuss, and provide recommendations about the impact of business analysis and its elements on management accounting and the accounting profession. The management accountant's role and responsibilities have evolved from simply reporting overall historical figures, to include measuring organizational performance and providing information relevant to management decision making. proposes a Managerial Accounting Data Analytics (MADA) framework based on the balanced scorecard theory in the context of business intelligence. Information is derived from publications by the American Accounting Association, Emerald, Elsevier,. in international journals indexed by Scopus. The 2010-2022 sample included up to 30 articles on analytic of costing system design. This paper contributes to research by examining the influence of business analytics on managerial accounting in the context of enterprise systems. This study presents a Managerial Accounting Data Analytics (MADA) framework that integrates